Can the Business Outlook Survey help improve estimates of the Canadian output gap? - Calista Cheung; Luke Frymire; Lise Pichette (Bank of Canada, 2021)
The output gap is a key variable used to assess inflationary pressures in the economy, but estimates in real time are subject to uncertainty and often revised significantly. This paper assesses whether questions in the Bank of Canada's Business Outlook Survey (BOS) can provide useful signals for broader capacity pressures in the economy. The concept of capacity pressures is captured in the BOS through various questions on firms' ability to meet demand and labour shortages. In particular, we examine whether these BOS questions, as well as a summary measure of the BOS results, produce information that can be used to improve real-time output gap estimates for Canada. We find that survey data help predict the various measures of the output gap used by the Bank of Canada. This supports the Bank's practice of using information contained in the BOS to refine its assessment of the current state of the economic cycle. It further provides a framework for incorporating the survey information into quantitative estimates of the output gap.
Keywords: E3; 330; Business fluctuations and cycles; Central bank research; Economic models; Monetary policy and uncertainty; Potential output